(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective. To evaluate the relationship between fluoride concentration in drinking water wells and the degree of dental fluorosis in 504 students aged 12-15 years from different schools in Arequipa. Methods. In this observational epidemiologic study, we evaluated water samples that were subjected to laboratory analysis to determine the amount of fluoride in mg/l. The average age of the participants was 13.55. Results. There were normal fluoride concentrations in three wells in Pachacutec and two wells in Tiabaya. The highest frequency would have a mild degree of fluorosis followed by a very mild degree; 5 out of 100 students would have a severe degree of anomaly. In the water wells with the highest fluoride concentration, without exceeding the allowed limits, the degree of severe fluorosis was more frequent than in other concentrations. As fluoride concentration decreases, the degree of normal fluorosis increases and the severe degree decreases to 0, but it is not permissible according to the standards set internationally. Conclusion. The higher concentration of fluoride in drinking water is directly related to the higher degree of fluorosis.